Promotion and Protection of Human Rights Through Education - Shyam, Mamta (Journal of Commerce and Trade, 2021)
Human rights are generally understood as the basic fundamental rights that cannot be denied to a person by any person or any government just because he is a human being. They are universal and are the same for all. Human rights include both rights and obligations. Education has a very important role in the promotion and protection of human rights. Education makes us aware of our civil and political rights which are often referred to as first-generation rights and second-generation rights as social, economic and cultural rights. Without proper education, one cannot be dealt with these essential philosophical and basic rights and obligations. The concept of human rights extension through education now popularly exists and has traveled to include it as third-generation rights. The relationship between education to understand and the right to learn should be emphasized without which education is incomplete. An educated civilization can only know its rights and therefore knows to defend it. The human rights-based approach to education assures every child a quality education that respects and promotes his right to dignity and optimum development. The right to education has been marked as a priority on the agenda of the international community because the right to education is not only a human right in itself, but also transcendent to exercise all other human rights. Human rights are the basis of human values, discipline and dignity. Classification-JEL : J2, K38, I24, I28